Efek Pelanggaran Standar Akuntansi Pemerintahan dan Ketidakpatuhan Peraturan terhadap Opini Audit Laporan Keuangan di Sulawesi Selatan - Achdian Anggreny Bangsawan; Ahmad Abbas (Jurnal Akuntansi dan Pajak, 2021)
This research aims at testing the effect of the violation of governmental accounting standard and the incomplianece with the regulation on the opinion audit of financial statements in South Sulawesi. The type of this research is quantitative. The sample of this research was local government employing the data of financial statements. The data were analyzed using ordincal logistic regression. The results of this research found that the violation of governmental accounting standard and the incomplianece with the regulation have negative effect on the opinion audit of financial statements. The higher the findings related to the violation and the incompliance, the lower the local governments accept the unqualified opinion.